Reaffirmation of the Direct Horizontal Effect of the General Principle of Non-Discrimination in EU Law: Comment on the Case C-193/17 Cresco Investigation Gmbh v. Markus Achatzi (Polish Yearbook of International Law, 2021)
The relevant ruling concerns discrimination based on religion, in particular the question of the incompatibility of national legislation with EU Directive 2000/78. Following a short presentation of the factual background, the opinion of the Advocate General, and the judgment of the Court, the article offers comments on questions raised in the judgment, including the direct horizontal effect of the general principle of non-discrimination. In its previous case law the Court confirmed that the principle has “the horizontal exclusion effect.” However, in Cresco Investigation the question was whether it can be the source of rights for individuals. The ECJ adopted a firm approach, ruling that the general principle of non-discrimination as enshrined in Art. 21(1) of the Charter is sufficient in itself to confer rights on individuals which can be invoked in disputes with other private parties. This means that the Court recognized “the horizontal substitution effect” of the general principle of non-discrimination, which is connected with both setting aside any discriminatory provision of national law and applying to members of the disadvantaged group the same arrangements as those enjoyed by persons in the privileged category. The possible consequences of this approach are discussed in the article.